Étude de la corrélation entre les précipitations, le débit fluvial et les paramètres morphométriques dans le bassin versant d'El Bared, Liban Nord à l’aide du SIG - Douha Akkari (VertigO, 2024)
This study examines the correlation between morphometric parameters and river flow in the El Bared watershed, located in the northern region of Lebanon, using geographic information systems (GIS). It aims to better understand the hydrological and geomorphometric dynamics of the region to anticipate the risks of flooding and soil erosion in the face of rapid environmental changes. The results reveal a significant correlation between morphometric parameters and hydrological regimes, highlighting the importance of geomorphology in the hydrological response of the basin. The study identifies distinctive characteristics of the El Bared basin, allowing floods to be classified as moderate power, which contributes to a better understanding of hydrological processes and recommendations for effective management of water resources in the region. More specifically, the analysis focuses on recurring floods along the Nahr El-Bared watercourse, attributed to the torrential nature of the hydrological regime, the intensity of precipitation, the steep topography and the melting of the snow cover. An observation over a period from 1999 to 2016 reveals that the most significant flood took place in February 2005, with a sudden increase in flow reaching 83.39 m3/s in one day. The results of the flood analysis show a correlation between abundant winter precipitation and the high number of floods in February and March, highlighting the significant impact of the number of rainy days on groundwater recharge and runoff. The study also examines flow and drainage systems in the context of a karst aquifer, highlighting specific features such as the separation of transmissive and capacitive functions. Temporal analysis of the flow of the Nahr El-Bared reveals an exponential drying curve, influenced by liquid and snow precipitation, as well as snowmelt. Additionally, the study evaluates methods for studying the rainfall-runoff relationship, highlighting an average delay of six days between heavy rains and consequent flooding, while highlighting the impact of other climatic factors such as temperature and the wind.